South-South Collaboration in CCAFS for developing capacity on weather index insurance - Vyas, Shalika; Shirsath, Paresh Bhaskar; Aggarwal, Pramod K. (2019)
Climate risk management has become a key area for research and policy dialogue due to increasing threats of disasters and climate extremes, which are likely to increase due to climate change. Global south (including Latin America, Africa, South and South-east Asia) is a major hotspot for climatic risk challenges due to high exposure to climate extremes when compared to temperate regions, high incidences of poverty, poor enabling environments and low regulatory support. With this backdrop, the CGIAR Research Program Climate Change, Agriculture and Food Security (CCAFS) has been working in Africa, Latin America and Asia together with its partners on accelerating climatic risk management through a dedicated research flagship to Climate services and safety nets. A workshop was thus organized by CCAFS to mobilize stakeholders in different regions to facilitate the diffusion of learnings and advances in climate risk management from one region to another. This workshop was planned after feedback and follow-up from South: South collaboration on climatic risk management workshop in New York, concurrent with the needs and demands of the stakeholders.